PENGGUNAAN PROGRAM KOMPUTER MICROSOFT OFFICE PADA PERHITUNGAN UJI BELAH BETON DENGAN BAHAN TAMBAH LIMBAH CAIR PABRIK GULA (TETES TEBU) - Marwahyudi, Marwahyudi; Yulianto, Arif (2086-4221, 2013)
Sugar factory waste is pretty exciting stuff for in the analysis. Waste generated solid, gas, liquid still need to utilize the waste handling. On this occasion, the researcher tried to analyze molasses added to concrete materials. In this study, we created two groups of specimens will be compared to the results which one is better. Then the object tested sectioned with a compression test machine. After investigation it turned out the result showed the difference between concrete with molasses added material would be better than ordinary concrete. Top Calculation results divisive 15.63 Kg/cm2  test without added ingredients and 33.71 Kg/cm2concrete with molasses added ingredients.